Multigroup Analysis (MGA) of the Effect of Self-efficacy on Entrance Test anxiety by Separating Boys and Girls with the Mediating Role of Emotion Regulation - Naseri, Zahra; Mashhadi Farahani, Zahra; Saeidinia, Sara; Panahi, Mona; Gholami Zarashki, Zahra (International Journal of Education and Cognitive Sciences, 2025)
Purpose: Test anxiety is a prevalent and significant issue in education, and it is closely connected to the academic success and advancement of numerous students. This study aims to explore how self-efficacy influences test anxiety in both male and female teenagers while considering the role of emotion regulation as a mediator. Methods and Materials: The research conducted was a descriptive-correlational study utilizing a cross-sectional research methodology. Structural equation modeling (SEM) and multi-group analysis (MGA) were employed. The statistical population consisted of high school students in Tehran studying experimental, mathematical sciences, and humanities between October and November 2023. A sample of 187 adolescents was selected using a multi-stage cluster sampling technique. Research instruments utilized were the General Self-Efficacy Scale (GSE-17), Test Anxiety Questionnaire (TAQ), and Cognitive Emotion Regulation Questionnaire (CERQ). Descriptive statistics were analyzed using SPSS version 27 software, while the path between variables and Multi-Group Analysis (MGA) was conducted using SmartPLS version 4 software. A p-value of 0.05 was deemed appropriate for the study. Findings: The study findings indicate that self-efficacy had a negative and significant impact on test anxiety, mediated by the variable of other blame. However, there was no discernible distinction between the male and female groups, as shown by the minimal difference (Difference = -0.080, P = 0.604). Conversely, self-efficacy exhibited a negative and significant influence on test anxiety through the refocus on the planning variable, with a noticeable contrast between the boy and girl groups (Difference = -0.255, P = 0.020). Consequently, it can be inferred that the refocus on the planning variable may serve as a mediator solely in the male group, resulting in a decrease in test anxiety levels among boys. Conclusion: According to the findings of this study, it is evident that both self-efficacy and emotional regulation play a role in influencing test anxiety. Therefore, it is important to consider these factors in the treatment and understanding of students' anxiety.